THE INTERACTION OF TURBULENCE STREAM WITH A SHOCK WAVE - Касьянов, В. О.; Хасанов, Р. Р. (Science-based technologies, 2010)
The interaction of isotropic turbulence with a shock wave is investigated. Possibility of generation of sound is examined. The shock wave surface nonstationarity has been modeled and some substantial features of stream af-ter the shock appeared. In particular the change of intensity of turbulence as a result of gas flowing through the shock is studied. The simple enough model of turbulent indignation, got on the basis of linearisation of Nave—Stok, has been offered in theoretical part of the work. It is foreseen that the practical use of work might be possi-ble in external acoustics of aviation gas-turbine engines.